Conocimientos y prácticas del enfermero sobre procedimiento de aspiración de secreciones orofaríngeas en emergencia EsSalud Iquitos 2024 - Hidalgo Cárdenas, Johan Lovis (2025)
The objective was to determine the relationship between nursing knowledge and practice regarding the oropharyngeal secretion aspiration procedure in emergency patients at EsSalud Iquitos 2024. The study was quantitative with a non-experimental, descriptive, correlational, and cross-sectional design. The sample consisted of 81 nurses working in EsSalud's emergency services. The techniques used were survey and observation. The data collection instruments used were the nurses' knowledge questionnaire on the oropharyngeal secretion aspiration procedure in emergency patients at EsSalud Iquitos and the checklist or observation list on the oropharyngeal secretion aspiration procedure used by emergency nurses at EsSalud Iquitos. SPSS version 27.0 statistical software was used for data processing. For bivariate analysis, Kendall's Tau-b statistical test was used for ordinal variables. The alpha (α) significance level is 0.05. The results show that regarding the level of knowledge on the procedure for aspiration of secretions, 48.1% showed an average level of knowledge. Regarding practice, 63.0% (51) demonstrated incorrect practice. In conclusion, it was shown that there is a significant statistical relationship between the knowledge and practice of nurses on the procedure for aspiration of oropharyngeal secretions in emergency patients Essalud Iquitos 2024, with a Kendall's Tau-b significance value of 0.028 (p < 0.05).